The lived experience of delirium in intensive care unit patients: A meta-ethnography. Issue 2 (March 2020) - Gaete Ortega, Damaris; Papathanassoglou, Elizabeth; Norris, Colleen M.
Abstract: Objectives: The objectives were to interpretatively synthesise qualitative findings on patients' lived experience of delirium in the intensive care unit (ICU) and to identify meanings and potential existential issues that affect them during and after their experience. Patients may face existential challenges when they are vulnerable in their confusion, all while confronting the reality of their mortality in the critically ill state. Review methods: The study involved meta-ethnographic synthesis of published qualitative studies addressing the lived experience of delirium for patients in ICU based on a systematic literature search. Data sources: MEDLINE, PsycINFO, Embase, Scopus, CINAHL, ProQuest, and Cochrane were the sources. Studies were selected based on the predefined inclusion/exclusion criteria. The identified studies were subjected to a quality appraisal based on a Critical Appraisal Skills Programme tool. Results: Based on the eligibility criteria, nine qualitative studies were included, of overall medium to high quality. One core theme, "a perturbing altered reality" and four main themes were identified: "disturbed sense of time", "omnipresent feeling of fear", "impact of human connection", and "perceiving surreal events". These four themes illustrate how the three salient existential issues of uncertainty, self-perceived helplessness, and death that are present in delirium make it a highly distressing experience for patients in ICU. Conclusions: Critically ill patients who experience delirium appear to face intense existential issues, which may not be identified by care providers and may remain unaddressed during their ICU stay and after discharge. Patients report that addressing the memories of these issues would be therapeutic. Future research needs to explore care approaches to meet the unique psychosocial needs of critically ill patients with delirium.